(untitled) (Modern education and development, 2025)
In this article, it was clearly discussed about core issues that school students come across while learning modern English. Because of technology, students are exposed to a lot of different online websites, online games, and social media, so they are involved in informal language a lot. The article integrates student surveys, teacher interviews, and writing samples to identify why students confuse with formal language and informal language. According to results, most of school students use informal spelling, grammar, and slang words in their academic writings. Teachers also mentioned that some students are addicted to AI a lot, so they just copy the assignment and do not realize what thing they did in their tasks. The study concludes that even though modern English provides different opportunities to learn language effectively, students are required instructions for the usage of correct English. In the recommendation part, teachers and schools are recommended to develop English learning by involving real-life examples and teaching the variation between formal and informal English.